Analisis Kualitas Air Limbah Industri Pupuk Npk Padat Pada Sungai Gembolo Menggunakan Software Mike21 - Firza Ramadhan (Prosiding ESEC, 2023)
Gembolo River is one of the rivers that flows across Pungging District, Mojokerto Regency. At present the Gembolo River is experiencing a decline in river water quality caused by the disposal of waste water from both industrial and domestic activities. The decline in the quality of the Gembolo River water can be seen through the color of the water and its smell. Industrial development in Mojokerto Regency is one of the biggest factors besides the domestic activities of the community that occur around the river flow. There are various industries that exist along the river flow and affect the water quality of the Gembolo River, one of which is the solid NPK fertilizer industri. The treated wastewater from the Fertilizer Industri Wastewater Treatment Plant (WWTP) is channeled directly to the Gembolo River. This study aims to determine the effect of the distribution of wastewater on the water quality of the Gembolo River produced by the solid NPK fertilizer industri by conducting river water modeling. The measurement of the distribution of wastewater uses a quantitative descriptive method using Mike21 software. The results of the research on the water quality of the Gembolo River found that influenced by time, discharge, and length of the river, the discharge of solid NPK fertilizer industri wastewater did not significantly affect the water quality of the Gembolo River. In addition, the existence of other industries in the upstream and downstream of the river also has a significant effect on the water quality of the Gembolo River.